Health Security as a Global Public Good in the Conditions of the Revolution 4.0 - Giacomuzzi, Salvatore; Rabe, Martin; Titov, Ivan; Zozul, Tamila; Kokhan, Marianna; Zyhaylo, Natalya; Barinova, Natascha; Sedykh, Kira; Kocharian, Oleksandr; Kechur, Roman; Garber, Klaus; Stix, Rüdiger; et al. (Journal of Public Governance, 2023)
Objectives: Although the concept of health security is becoming accepted in public-health-related literature and practice, there is no full agreement on the scope and content. The aim of this paper is to draw attention to the definition of health security and its role within the Revolution 4.0. Research Design & Methods: This is a theoretical article and as such addresses a problematic situation concerning missing standards in health security and the Revolution 4.0. Findings: The WHO (2018) has stated unequivocally that ‘functioning health systems are the bedrock of health security’. The authors attempt to prove that health security in the conditions of the Revolution 4.0 needs to be defined more precisely and has to be implemented as a global public good nationwide with accepted minimal standards. Implications / Recommendations: H ealth security belongs to the sphere equally important to that of the Revolution 4.0. A concept of Health Security that is not widely accepted and implemented creates a problematic mélange for employees as well as for industrial development. These features will be considered. Contribution / Value Added: This paper tries to underline the relative shortage of common agreements on health within the Revolution 4.0.